MANAGEMENT OF SEPTIC SHOCKAND HYPOXIA INDUCED CONJUGATED HYPERBILIRUBINAEMIA IN CASE OF MAJOR CHEST TRAUMA – CASE REPORT - Kantor, Tibor; Gergely, Istvan; Denes, Marton; Kantor, Katalin; Torok, Arpad; Sandor, Zuh; Pop, Tudor Sorin (European Scientific Journal, ESJ, 2015)
This case report describes a 50-year-old male trauma patient with multiple crushed thoracic lesions: flail chest, bilateral hemopneumothorax, myocardial infarction and pulmonary contusion. In the ICU he developed ARDS and pulmonary infection which lead to septic shock. Hypoxia due to inadequate ventilation and reduced visceral perfusion due to shock induced elevated levels of conjugated bilirubin. Continuous veno-venous hemofiltration (CVVH) sessions in combination with CytoSorb® filters and MARS® were needed. After surgical fixation of the flail segment ventilatory parameters improved significantly.